Effect of routine pre-operative urethral catheterization of women undergoing minor gynaecological surgeries on urinary symptoms and urinary infections: a randomized control study - Faza, Mohannad Abu; Abdelazim, Ibrahim A.; Aziz Khalifa, Amr A.; Othman, Hossam S.; Alsharif, Dareen A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of urinary tract infection increases in young sexually active women, and women with previous UTI. Routine urethral catheterization performed for bladder evacuation before minor gynecological procedures and it is not clear whether this routine urethral catheterization associated with increased incidence of bacteriuria or UTIs or not. This study designed to detect the effect of routine uretheral catheterization for women undergoing minor gynecological surgeries on urinary symptoms and urinary infections. Methods: Two hundred and forty women infertile women scheduled for uterine assessment by diagnostic hysteroscopy before in-vitro fertilization in assisted reproduction unit of Ahmadi Hospital, Kuwait Oil Company were included in this study. Participants were randomized into; group I (catheterized group) and group II (non-catheterized group). Participants’ urine samples compared pre-operatively and post-operatively and they asked to complete about their pre and post-operative urinary symptoms. Results: Post-operative dysuria, frequency and urgency were significantly higher in catheterized group (22 (18.33%), 26 (21.66%) and 18 (15%); respectively) compared to non- catheterized group [5 (4.16%), 7 (5.83%) and 4 (3.33%); respectively]. Relative risk of dysuria, frequency and urgency after catheterization were 4.4, 3.7 and 4.5; respectively (95% CI; 1.7-11.2, 1.67-8.22 and 1.56-12.9; respectively). Asymptomatic bacteriuria, UTIs and subsequent need for antimicrobial therapy were also significantly high in catheterized group [15 (12.5%), 18 (15%) and 18 (15%); respectively) compared to non-catheterized group (3 (2.5%), 2 (1.96%) and 2 (1.96%); respectively]. Relative risk of asymptomatic bacteriuria and UTIs after catheterization in women undergoing minor gynecological procedures were 5 and 9; respectively (95%CI; 1.48-16.8 and 2.1-37.9). Conclusions: Catheterization in women undergoing minor gynecological surgery was associated with increased risk of dysuria, frequency, urgency, ASB, UTIs and subsequent antimicrobial therapy. Surgeons should revise the practice of routine preoperative catheterization for women undergoing minor gynecological procedures.